Legal Drafting Berbasis Artificial Intellegence: Peluang dan Tantangan di Indonesia - Saputra, Dimas Alan (UNIVERSITAS SERAMBI MEKKAH, 2025)
This paper aims to analyze the position and impact of Artificial Intelligence in the drafting of legal documents. In this research, it is a qualitative research method with a descriptive approach that aims to provide a detailed explanation of material related to AI-based legal drafting with opportunities and challenges in Indonesia. Artificial Intelligence is an innovation that can facilitate human work, but its use must be regulated by specific rules to minimize potential threats or negative effects, which can be mitigated through established regulations. Moreover, Artificial Intelligence is limited to being a supportive tool in the formation of legal documents, as it is almost impossible to consider AI as a subject capable of creating legal documents. In the end, Artificial Intelligence remains a tool to assist humans. Meanwhile, the application of Artificial Intelligence in the legal field has already begun in Indonesia.